2005
DOI: 10.1002/ange.200462602
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscaffold Mediates Hydrogen Release and the Reactivity of Ammonia Borane

Abstract: The increasing demand for clean energy sources that do not add more carbon dioxide and other pollutants to the environment has resulted in increased attention worldwide to the possibilities of a "hydrogen economy" as a long-term solution for a secure energy future based on potentially renewable resources. [1][2][3] Some of the greatest challenges are the discovery and development of new on-board hydrogen-storage materials and catalysts for fuel-cell-powered vehicles. New materials that store both high gravimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(174 citation statements)
references
References 24 publications
3
165
0
6
Order By: Relevance
“…The detrimental side products of borazine and diborane could be detected during the AB thermolysis. Compared with the neat AB, MIL-101 and Ni@MIL-101 doped with AB samples start to evolve H 2 at about 50 C and give broad desorption peaks centered at 85 and 75 C which are lower than other AB nanocomposite systems [20,21,32]. This is the first report of such a big decrease (40 C) in the decomposition temperature, which (75 C) is lower than PEMFC working temperature (80 C).…”
Section: Dehydrogenation Propertiesmentioning
confidence: 76%
See 3 more Smart Citations
“…The detrimental side products of borazine and diborane could be detected during the AB thermolysis. Compared with the neat AB, MIL-101 and Ni@MIL-101 doped with AB samples start to evolve H 2 at about 50 C and give broad desorption peaks centered at 85 and 75 C which are lower than other AB nanocomposite systems [20,21,32]. This is the first report of such a big decrease (40 C) in the decomposition temperature, which (75 C) is lower than PEMFC working temperature (80 C).…”
Section: Dehydrogenation Propertiesmentioning
confidence: 76%
“…In AB/SBA-15 system, the obtained results showed that borazine neither occurred in the volatile products nor was confined in the SBA-15 framework [20], indicating …”
Section: 3mentioning
confidence: 91%
See 2 more Smart Citations
“…One known approach is to incorporate hydrogen storage materials into nanoporous materials. It was first applied in the NH 3 BH 3 system [211] and good improvement was obtained: The dehydrogenation temperature was largely decreased and the amount of borazine gas (an impurity) was significantly reduced. Recently, this approach was introduced for M(BH 4 ) n materials, and some recent achievements [160,[212][213][214][215][216][217][218][219][220][221][222] are summarized in Table 6.…”
Section: Promoting Kineticsmentioning
confidence: 99%